Study On The Possibility Of Establishing Shipbuilding Cluster In Lampung Province Sumatra Indonesia As Pilot Project In Conjunction With Government’s Program On The Acceleration And Expansion Of Indonesian Economic Development (MP3EI) - Sunaryo, Sunaryo (Diponegoro University, 2013)
As the result of the implementation of cabotage principle in 2005 by the Government of Indonesia the number of national fleet has increased dramatically around 5,000 units in the last five years due to import of used vessels from abroad, which most of them are relatively old and need renewal, maintenance and repair. This situation creates potential market for new building as well as repair yards in Indonesia. In response to this the research is aimed to identify the possibility of establishing a shipbuilding cluster in Lampung Province, Sumatra as pilot project for the Government’s program in developing the shipbuilding industries in Java and Sumatra Economic Corridors of the Acceleration and Expansion of Indonesian Economic and as complementary to the existing shipbuilding centers in Batam, Jakarta, East Kalimantan and Surabaya to cater the demand, and to make the most of industries around it. The study is started by gathering primary and secondary information regarding the location, market, resources and infra structure, and supporting industries, simulating the information, draw conclusions, and propose a conceptual design of the cluster.